An architecture manifesto critical reason and theories of a failed practice - Lahiji, Nadir 1948- (Routledge, 2019)
What is a manifesto? In basic terms, a manifesto is 'the invention of future for the present'. We have been oblivious to the fact that the twentieth century was the century of manifestos. It was the century of programmatic declarations, radical and avant-garde political, artistic and architectural proclamations. Manifestos came to be a genre of concise and radical-critical writings exposing the repressed contradictions in a dominant doctrine. They opened up the present to the future by denouncing the forces of the status quo and offering alternative programs. Today, this genre is a more valid, even urgent, form of writing for our time, in order to expose the dominant doctrine that has closed the future in subscribing to the ideology of the 'end of history'. In this manifesto, Nadir Lahiji takes a leap of faith. It is a faith in Lost Causes. He asserts that today, architectonic reason has fallen into ruins. As soon as architecture leaves the limits set to it by architectonic reason, no other path is open to it but the path to aestheticism. This is the wrong path contemporary architecture has taken. In its reduction to a pure aesthetic object, architecture negatively affects the human sensorium. Capitalist consumer society creates desires by generating 'surplus-enjoyment' for capitalist profit and contemporary architecture has become an instrument in generating this 'surplus-enjoyment', with fatal consequences. This manifesto is thus both a critique and a work of theory. It is a siren, alarm, klaxon to the current status quo within architectural discourse and a timely response to the conditions of architecture today